Association of tobacco use with depressive symptoms in adults: Considerations of symptom severity, symptom clusters, and sex - Shakila Meshkat; Qiaowei Lin; Vanessa K. Tassone; Reinhard Janssen-Aguilar; Hilary Pang; Wendy Lou; Venkat Bhat (PLoS ONE, 2025)
Objective We aim to assess the association between depressive symptoms, depressive symptom severity and symptom clusters with tobacco use. We will also evaluate sex differences in these associations. Method This cross-sectional study used data from the National Health and Nutrition Examination Survey (2005-2018). Depressive symptoms were assessed using the Patient Health Questionnaire-9. Tobacco use was categorized into four groups: cigarette use, smoked tobacco products (pipes and cigars), smokeless tobacco products (chewing tobacco and snuff), and non-tobacco use (reference group). Results This study included 33,509 participants. Cigarette use was associated with a 0.83-unit increase in total PHQ-9 scores (95% CI =  [0.63, 1.04]), and 1.73 times higher odds of reporting depressive symptoms (95% CI =  [1.48, 2.02]) compared to non-tobacco use. However, the use of smoked and smokeless tobacco was not associated with depressive symptoms. In females, cigarette use showed a stronger association with total PHQ-9 scores (aCoef =  1.23, 95% CI =  [0.92, 1.55]) than in males (aCoef =  0.45, 95% CI =  [0.21, 0.69]). Additionally, female smoked tobacco users showed positive associations with both PHQ-9 scores and the presence of depressive symptoms, but this relationship was not observed in males. Furthermore, subgroup analysis revealed associations between cigarette use and cognitive-affective and somatic symptom clusters, as well as a relationship between the logarithm of total cigarette consumption and depressive symptoms. Conclusion Cigarette use was associated with higher odds of depressive symptoms with females having a stronger association. Further studies are needed to replicate these findings and examine the underlying mechanisms.